What pollinators see does not match what they smell: Absence of color-fragrance association in the deceptive orchid Ionopsis utricularioides. (February 2021) - Aguiar, João Marcelo Robazzi Bignelli Valente; Ferreira, Gabriel de Souza; Sanches, Patricia Alessandra; Bento, José Mauricio Simões; Sazima, Marlies
Abstract: Many deceptive orchids present variation in floral color and fragrance. This might be advantageous for the plant, as it can disturb the associative avoidance learning of pollinators, promoting more visits to the flowers. Some studies have shown that color and fragrance can be correlated in polymorphic deceptive orchids, but these studies employed color traits based on the human visual system and not the visual perception of pollinators. Thus, we investigated the composition of the floral fragrance of Ionopsis utricularioides (Sw.) Lindl., a polymorphic deceptive orchid, and analyzed possible correlations with the floral color as seen by bees, Apis mellifera L. and Melipona quadrifasciata Lepeletier, using the color hexagon model. We found high color and fragrance intraspecific variation, as expected for deceptive species. However, we found no color-fragrance association in individuals, either by comparing fragrance profiles with the color variable saturation or by comparing them with the placement of individuals in the color hexagon for both bee species. This lack of correlation contradicts the biochemical pathway hypothesis, which proposes that associations between floral color and scent in polymorphic flowers arise from shared biochemical pathways. However, a complete absence of correlation between floral signals is consistent with selection arising through pollinator cognitive ecology. Lack of correlation would increase the floral variability perceived by bees, given their multimodal learning, and this variability could disrupt avoidance learning of deceptive flowers, thus enhancing the efficacy of the plant's deceptive pollination mechanism. Graphical abstract: Image 1 Highlights: Floral volatiles are compared to orchid's colors as seen by pollinators. No correlation was found between fragrance and color. This is contrary to the sharing of chemical pathways hypothesis. The absence of correlation could increase the level of perceived variability. This could further enhance the deception mechanism.